Predictors of the Effectiveness and Efficiency of Student Affairs and Services (SAS) among Higher Education Institutions (HEI’s) - Flora H. Salandanan; Lerma P. Buenvinida; Marcial M. Bandoy (Research Synergy Foundation, 2021)
Exploring new innovative and learning modalities is an urgent move of higher education as an option in this pandemic. As a result, to flexible delivery of Student Affairs and Services as stated in CMO 8 s., 2021, Guidelines on the Implementation of Flexible Delivery of student Affairs and Services, (SAS) programs during the Covid-19 epidemic as the continuity of student services is significant to the overall development of students during this trying time. The predictors of student affairs and services (SAS) performance among higher education institutions (HEIs) were determined using a descriptive-correlational research method. The students in the College of Teacher Education and Student Affairs and services (SAS) Unit head and staff were selected as respondents through stratified random sampling. The findings revealed that the majority of the student respondents are from HEI’s in the Province of Laguna. There is a significant relationship between the students’ affairs services in terms of Information and Orientation Services, Guidance and Counselling Services, Student Training, Student Organizations and Activities, Admission Services, Scholarships and Financial Assistance (SFA) and the effectiveness and efficiency of student affairs services. As recommended, the Guidance and Counselling unit must administer the student assessment tools regularly and periodically to determine the appropriate interventions necessary in the new normal. The promotion of mental health among students through different platforms may intensify more. The HEI’s and SAS may consider strengthening downloadable materials and their contents as means of student orientation and information dissemination; online seminars, workshops, and conferences relative to students’ program, specialization, and other relevant topics; enhance the system of recognition and accreditation, supervision, monitoring of student organizations and evaluation of its activities.